Antibacterial activity of Garcinia kola and Hunteria umbellata extracts on bacterial isolates from consumed sachet water in Edo State, Nigeria - Tosan Mercy AKIRI-OBAROAKPO; Emmanuel Esosa IMARHIAGBE; Blessing Miesieyefa OFFEH (Studia Universitatis Babeș-Bolyai. Biologia, 2023)
Water is an essential resource and its purity should not be negotiated when it comes to human consumption. This study investigated the antibacterial activity of Garcinia kola and Hunteria umbellata seed and epicarp on some bacterial isolates from sachet water. Duplicate samples of ten brands of sachet water were purchased from sales outlets around Ugbowo community, Benin City. Plate count techniques, minimum inhibitory and minimum bactericidal concentrations of the extracts were adopted in this investigation. Heterotrophic bacterial counts revealed highest range of 3.72±0.50x102 cfu/mL in EJ water and lowest in IB water (0.00±0.0x102 cfu/mL) while total coliform counts revealed its highest value in EJ water (3.62±0.30x102 cfu/mL) and lowest value (0.00±0.0 x102 cfu/mL), in OL, IB, NOS and UNI water. Aeromonas sp., Bacillus sp., Pseudomonas sp., Staphylococcus aereus and Enterobacter sp. were isolated. The antimicrobial susceptibility profile revealed varying zones of inhibition of 4 mm for Aeromonas sp., for Garcinia Kola and 20 mm recorded against Staphylococcus aureus and Bacillus sp. for Hunteria umbellata epicarp extract. The Minimum Inhibitory Concentration of susceptible bacteria to Hunteria umbellata and Garcinia kola extract were 6.25mg/mL and 12.5mg/mL, respectively, except Aeromonas sp. which had 50 mg/mL. Hunteria umbellata epicarp had a greater bactericidal effect of 6.25mg/mL against Staphylococcus aureus, while Garcinia kola had its greatest bactericidal effect on Enterobacter sp. with a minimum bactericidal concentration of 12.5mg/mL. This study has revealed the potentials of Hunteria umbellata epicarp and Garcinia kola as effective natural therapeutic agents against some harmful bacteria, preventing their pathogenic effect.